Bacterial diversity in different growing mediums of oil palm seedlings associated with potassium use efficiency - SRI WENING; RETNO DIAH SETIOWATI; DIAN RAHMA PRATIWI; IKHWAN FADLI PANGARIBUAN; EKO NOVIANDI GINTING (Society for Indonesian Biodiversity, 2024)
Abstract. Wening S, Setiowati RD, Pratiwi DR, Pangaribuan IF, Ginting EN. Bacterial diversity in different growing mediums of oil palm seedlings associated with potassium use efficiency. Biodiversitas 25: 3386-3393. Plant genotype, environmental conditions, and agronomical practices influence nutrient use efficiency. Understanding whether specific microbial communities support the nutrient use efficiency of specific genotypes is very important. This study aimed to understand the bacterial diversity in three different growing mediums of oil palm seedlings with potassium-use efficient characters. The three kinds of medium were medium 1 (sandy soil, recommended dose of fertilizer except for potassium (75% of a recommended dose of potassium)); medium 2 (sandy soil, recommended dose of fertilizer except for potassium (0% of potassium)); and medium 3 (topsoil, recommended dose of fertilizer at five months after planting). A metagenomic approach was conducted using a long-read sequencing platform, allowing the full-length 16S rRNA gene to be sequenced. The alpha diversity analysis showed that medium 3 had the most identified species, while medium 2 had the lowest. Based on the relative abundance, Lactobacillus helveticus was the most abundant species, and Lactobacillus was the most abundant genus in medium 1. Ralstonia pickettii was the most abundant species, and Dyella was the most abundant genus in medium 2. For medium 3, Chujaibacter soli was the most abundant species that dominated the bacteria community, and Lactobacillus was the most abundant genus. These findings were related to the bacteria's function in the respective medium for plant nutrient uptake or utilization. The number of shared species between medium 1 and medium 3 was the highest compared to other medium compositions. It suggested the specific relationship of the potassium-use efficient seedling with the characteristic of the growing medium and the most abundant species or genus of bacteria found. Further research is needed to understand the interactions and influences of bacteria and other microorganisms in the mediums, and the specific genus or species found in potassium-use efficient oil palm seedling mediums.